Minimally Invasive Approach of a Retrocaval Ureter - Fidalgo, N (2016)
The retrocaval ureter is a rare congenital entity, classically managed with open pyeloplasty techniques. The experience obtained with the laparoscopic approach of other more frequent causes of ureteropelvic junction (UPJ) obstruction has opened the method for the minimally invasive approach of the retrocaval ureter. In our paper, we describe a clinical case of a right retrocaval ureter managed successfully with laparoscopic dismembered pyeloplasty. The main standpoints of the procedure are described. Our results were similar to others published by other urologic centers, which demonstrates the safety and feasibility of the procedure for this condition.